Vocabulary Instructions for EFL Learners - Magdalena Kartikasari Tandy Rerung (Journal of English Language and Culture, 2017)
The importance of teaching vocabulary has been emerged since 1980s, however not much research evaluate its effectiveness for EFL learners. On the other hand, the knowledge of words is a fundamental tool in order to bridging the language gap and connecting the skills as well. The following research is intended to find out how much is the vocabulary size of the BBI students and its relation to their language proficiency. Furthermore, to find out the effectiveness of vocabulary teaching techniques applied in the classroom during their semester program. The outcomes of this research is hopefully could increase the learners’ vocabulary skill and help them to understand new words and communicate it properly. Keywords: vocabulary instructions, vocabulary size, language proficiency